Advances in the extraction, purification, structural characterization, and elucidation of the biological functions of polysaccharides from Hericium erinaceus - Yu, Panling; Ma, Jianshuai; Yang, Lin; Dong, Qin; Yu, Changxia; Zha, Lei; Xu, Baoting; Zhao, Yan (Frontiers in Nutrition, 2025)
Hericium erinaceus has a high food and ornamental value and considerable benefits upon consumption and in research. The high polysaccharide content in H. erinaceus gives this fungus unique physiological functions and a smooth, palatable texture; notably, H. erinaceus is a superior source of polysaccharides compared with fruits and vegetables. This review focuses on polysaccharides derived from edible mushrooms, an area that has received limited attention in the literature, which has predominantly focused on plant-derived polysaccharides. The relevant literature on the extraction methods, purification processes, structural characterization, and biological functions of H. erinaceus polysaccharides (HEPs) has been systematically collated and summarized. H. erinaceus polysaccharides have immunomodulatory, lipid-lowering, antioxidant, antitumor, anti-inflammatory, hypoglycemic, and intestinal regulation effects. The aim of this study is to review the research progress pertaining to H. erinaceus polysaccharides, providing valuable insights and inspiration for future studies in related fields.